Surgical Treatment of a Neuromucoepidermoid Carcinoma of the Left Main Bronchus via Posterolateral Thoracotomy in a 4-Year-Old Boy - Liebrich, Markus; Friedel, Godehard; Amrhein, Peter; Tzanavaros, Ioannis (The Thoracic and Cardiovascular Surgeon Reports, 2020)
We report the case of a 4-year-old boy with a neuromucoepidermoid carcinoma of the left main bronchus. Complete resection of the carcinoma and reconstruction of the carina between lower and upper lobe by means of an end-to-end anastomosis was performed via a left-sided thoracotomy.
Keywords: neuromucoepidermoid carcinoma; bronchus resection; child